2016
DOI: 10.1155/2016/1369589
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asymmetric Carbon Information on Supply Chain Decisions under Low-Carbon Policies

Abstract: Through the establishment of the leading manufacturer Stackelberg game model under asymmetric carbon information, this paper investigates the misreporting behaviors of the supply chain members and their influences on supply chain performance. Based on “Benchmarking” allocation mechanism, three policies are considered: carbon emission trading, carbon tax, and a new policy which combined carbon quota and carbon tax mechanism. The results show that, in the three models, the leader in the supply chain, even if he … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Du et al [40] found that the cap-and-trade scheme would constrain the total carbon emissions and promote low-carbon production simultaneously under certain conditions. Yang et al [41] put forward a new policy which combined carbon quota and carbon tax mechanism and study the misreporting behaviors under three different polices.…”
Section: Cap-and-trade Schemementioning
confidence: 99%
“…Du et al [40] found that the cap-and-trade scheme would constrain the total carbon emissions and promote low-carbon production simultaneously under certain conditions. Yang et al [41] put forward a new policy which combined carbon quota and carbon tax mechanism and study the misreporting behaviors under three different polices.…”
Section: Cap-and-trade Schemementioning
confidence: 99%
“…It can be found from (8) that the retailer's price increases with the manufacturer's wholesale price and the carbon emission level , since * / = 1/2 > 0 and * / = /2( + ) > 0. Although increasing the wholesale price will inevitably push up the retailer's price and reduce the demand in return, it can be compensated for by increasing the carbon emission reduction level.…”
Section: Solutions For Model I (Traditional Single-channel Supply Chain)mentioning
confidence: 99%
“…Interestingly, the retail price increases with , while it decreases with , , and . Based on the retailer's response function (8), we obtain the manufacturer's optimal decisions in Proposition 3. Corollary 4 indicates that the higher carbon price can stimulate the manufacturer to emit less carbon only when a certain condition, that is, > 0 is satisfied.…”
Section: Solutions For Model I (Traditional Single-channel Supply Chain)mentioning
confidence: 99%
See 2 more Smart Citations